Kearns–Sayre Syndrome with Bilateral Ptosis and External Ophthalmoplegia: A Rare Case Report: Poster Presentation - Case Report - Resident - Philipus Putra Raharjo; Yunia Mansyur; Batari Todja Umar (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Kearns-Sayre syndrome (KSS) is a rare genetic disorder caused by a deletion of mitochondrial DNA (mtDNA) segment, typically characterized by a triad of symptoms includes external ophthalmoplegia, pigmentary retinopathy and appeared before the age of 20. The prevalence rate is about 1–3 per 100.000 individuals. It was diagnosed based on clinical features and supported by biochemical, radiological, histologic, and molecular genetic tests. Case Illustration : 26-year-old male with bilateral ptosis, chronic progressive external ophthalmoplegia, pigmentary retinopathy was shown from ophthalmology examination and associated with hearing loss. Physical examination showed short stature, wasting, and weakness of limb muscles. MRI examination revealed focal brain atrophy on bilateral parietal regions. Discussion : Mitochondrial DNA defect led to dysfunction of the central nervous system, endocrine system, extraocular muscle, myocardium, skeletal muscle, and other multiple systems. The clinical findings in this patient are appropriate for classical signs and symptoms of KSS. Central nervous involvementis shown by the neuroimaging result. There is no cardiac involvement suggested by normal cardiology examination. Although muscle pathology and molecular genetic analysis can play a great role to diagnose KSS, the classical triad of clinical signs plus one of the other symptoms could establish KSS diagnosis. Conclusion : KSS is a rare genetic disorder and challenging to diagnose. However, if a patient presents with the classic triad of symptoms, clinicians should have a high level of suspicion for the disorder. Additionally, It is important to perform a thorough evaluation to rule out other conditions that can cause similar symptoms.